Tantangan dan Peluang Mewujudkan Akses Universal ke Layanan Kesehatan Berkualitas di Indonesia: Literatur Review - Wulan Septiana; Siti Nurul Azizah; Riswandy Wasir (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Universal Health Coverage (UHC) is health insurance that ensures that people get justice in promotive, preventive, curative and rehabilitative health services, quality at affordable costs because health services in Indonesia are not evenly distributed, especially in rural areas. The aim of this research is to realize universal access to quality health services in Indonesia. This research uses a literature review method with online searches using scientific databases, such as Pubmed and Google Scholar. Researchers used articles from 2019-2023. The results of this research were obtained from two previous articles, namely regarding the analysis of the principles of financing health services and health services to achieve Universal Health Coverage in Indonesia. So in conclusion, the principle of financing and health services must be carried out fairly in every community, both in urban and rural areas.